A 4-year biogeochemical time series in a eutrophic coastal basin (Bedford Basin, Nova Scotia, Canada) - Sebastian Haas; Brent M Robicheau; Subhadeep Rakshit; Jennifer Tolman; Christopher K Algar; Julie LaRoche; Douglas WR Wallace; Andrew Cogswell (PANGAEA, 2020)
This collection contains data from continuous SUNA nitrate (SUNA_nitrate_profiles.xlsx) and CTD sensor profiles (CTD_BIO_1999-2018.xlsx) as well as data from discrete depths (5 meters and 60 meters; BB_Dal_data_discrete_depths_surface_bottom.xlsx; BB_BIO_data_discrete_depths_surface_bottom.xlsx). All data are from Compass Buoy Station, Bedford Basin, Nova Scotia, Canada. BB_annual averages (annual_averages.xlsx) were calculated from part of the above data or, in the case of Sackville River discharge, from the Environment Canada database. CTD data as well as the long-term data from discrete water samples were provided by the Bedford Institute of Oceanography (BIO), Dartmouth, Nova Scotia, Canada. They were partly modified, e.g. through unit conversion, and the original data can be found on the BIO website: http://www.bio.gc.ca/science/monitoring-monitorage/bbmp-pobb/bbmp-pobb-en.php The oxygen sensor data as of March 2015 in the 4-year dataset (2014-2017) were cross-calibrated against oxygen concentrations from discrete samples analyzed by Winkler titration. All oxygen sensor data in the long-term dataset (1994-2018) rely on the factory settings of the sensor. The R script contains code for a biogeochemical model of Bedford Basin bottom water and instructions on how to run it. It requires input from the data sheet BB_2014to17_nutrients_umol_kg.xlsx (included in doi:10.1594/PANGAEA.914695). Descriptions on methodology can be found in Haas et al. (PNAS, 2021).